PERAN INTELLIGENCE QUOTIENTS (IQ) DAN EMOTIONAL QUOTIENTS (EQ) TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING. (Survey pada karyawan PT. Mas Agung Sejahtera di Madura) - Gazali Gazali; Nuzulul Qurnain (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2020)
This study aims to determine the effect of Intelligence Quotients (IQ) and Emotional Quotients (EQ) on Employee Performance mediated by Organizational Culture. This research uses a quantitative approach and the type of research is explanatory research. The research sample amounted to 90 employees of PT. Mas Agung Sejahtera in Madura, with the method used is saturated sampling. The type of data used in the form of primary data obtained from the distribution of questionnaires. Analysis of the data used is Path Analysis with SPSS tools. The results showed that Intelligence Quotients (IQ) had no direct effect on employee performance. Intelligence Quotients (IQ) have an indirect effect on Employee Performance through Organizational Culture. Emotional Quotients (EQ) have a direct effect on employee performance. Emotional Quotients (EQ) have an indirect effect on Employee Performance through Organizational Culture. Organizational Culture is able to mediate Intelligence Quotients (IQ) and Emotional Quotients (EQ) on Employee Performance.